Tindak Tutur Kata Sapaan Masyarakat Angkola Di Kota Padangsidimpuan - Siti Meutia Sari; Tinur Rahmawati Harahap; Nursaima (Journal Education Innovation (JEI), 2024)
Speech acts are a theory of language use put forward by John Langshaw Austin (1962) in his book entitled How to do things with words. In speech events, a number of components of speech are found. There are 16 components put forward by Hymes (1974), namely message form, message content, setting, scene, message sender, speaker, message receiver, interlocutor, intent, purpose, key, channel, form of speech, interaction norms, norms interpretation, and genre. These 16 elements are summarized into 8 speech components with the English acronym "SPEAKING". In this study using qualitative methods with descriptive analysis techniques. The data in this study include the greeting word Angkola in the people of Padangsidimpuan City and its use based on the context in the household realm and the transaction realm. Participatory observation methods apply recording techniques through disguises and inducements, and interview methods apply question-and-answer techniques. The greeting words that should be used in everyday life for the Angkola people have experienced a shift. The greeting words that should be used by the Angkola people in Padangsidimpuan City are: Ompung, Amang Inang, Amang uda, Amangtua, Inang uda, Inang tua, bujing, nantulang, tulang, inang tobang, bou, amangboru, anggi.